Mycological diversity in whole-plant corn silages inoculated with Lentilactobacillus buchneri or Lentilactobacillus farraginis - L.B. Morais; B.F. Carvalho; L.R. Batista; R.F. Schwan; C.L.S. Ávila (Arquivo Brasileiro de Medicina Veterinária e Zootecnia, 2024)
ABSTRACT The objective was to investigate the effect of wild lactic acid bacteria (LAB) strains on the fungal and chemical composition of whole-plant corn silage. Three treatments were evaluated: CON-without inoculation, LB-inoculated with Lentilactobacillus buchneri (CCMA 1366), and LF-inoculated with L. farraginis (CCMA 1362). The silages were stored for 29, 103, and 193 d. The highest acetic acid (19.7 g/kg DM) and 1,2-propanediol (6.3 g/kg DM) concentrations were found in the LF, the highest aerobic stability was observed in this silage after 29 d (158.3 h). The yeast population was below the detection level at 29 d in the LF and 103 and 193 d in all silages. Seven genera of filamentous fungi (FF) were identified before ensiling; none of these were found after ensiling. At 29 d, Monascus pilosus was identified in the LB after aerobic exposure but did not produce citrinin. At 103 and 193 d, there was Aspergillus fumigatus predominance. A. flavus was identified at 103 d in the CON and LB; none produced B1, B2, G1, or G2 toxins. LAB strains modified the silages’ chemical and FF composition, and LF increased aerobic stability and reduced FF’s yeast population and diversity.